2018
DOI: 10.24170/15-2-3045
|View full text |Cite
|
Sign up to set email alerts
|

Long term outcome and EuroSCORE II validation in native valve surgery for active infective endocarditis in a South African cohort

Abstract: There has been little change in the mortality from infective endocarditis, despite the diagnostic and therapeutic advances made in the last 25 years. The current in-hospital mortality rate for patients with IE is 15% -20%, with 1-year mortality approaching 40%. The morbidity associated with infective endocarditis includes: valvular incompetence, embolisation, cerebrovascular accidents and congestive heart failure which have influenced the surgical approaches to a great extent. Infective endocarditis is a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 22 publications
2
13
0
1
Order By: Relevance
“…Approximately half of patients presenting with IE in the developed world, require surgery (22,24). This is similar to the rates reported for patients in South Africa (5,6), although our current experience is that the majority of patients will require surgery.…”
Section: Surgical Therapysupporting
confidence: 79%
See 3 more Smart Citations
“…Approximately half of patients presenting with IE in the developed world, require surgery (22,24). This is similar to the rates reported for patients in South Africa (5,6), although our current experience is that the majority of patients will require surgery.…”
Section: Surgical Therapysupporting
confidence: 79%
“…A prospective observational trial of patients with IE conducted at Tygerberg Hospital, Cape Town, South Africa reported a mean age of 37.7 years-72% of patients had underlying RHD (5). A more recent study conducted in Cape Town, South Africa revealed similar results with up to 80% of patients with NVE having evidence of underlying RHD (6). The Echoin-Africa (EIA) study screened over 6,000 secondary school pupils in the Tygerberg Hospital referral network (Cape Town, South Africa) and found a prevalence of 20/1,000 of pupils screened to have borderline or definite RHD, as per the World Health Federation criteria (7) for the detection of RHD (unpublished data).…”
Section: Patient Profilementioning
confidence: 91%
See 2 more Smart Citations
“…Dessa forma, ainda que a taxa de mortalidade observada tenha sido estatisticamente significativa, nossos resultados foram menores que no estudo do EuroSCORE II (Nashef et al, 2012) que a mortalidade em 30 dias e 90 dias foi 4,04% e 6,02%, respectivamente. Os resultados deste estudo foram mais baixos também quando comparados com resultados de um estudo realizado no sul africano, onde a mortalidade aos 30 dias e 90 dias foi 11% e 15%, respectivamente (Koshy et al, 2018).…”
Section: Critérios De Seleçãounclassified